Complex assessment of athletes' operative status and its correction during competitions, based on the body impedance analysis - Olena Dorofieieva; Kseniia Yarymbash; Iryna Skrypchenko; Marko Joksimović; Aneliia Mytsak (IP Iermakov S.S., 2021)
Background and Study Aim. The aim of this research was assessment and correction of highly skilled swimmers' operative status during competitions. Material and Methods. The authors carried out complex assessment of 46 high-skilled swimmers during competition period. The body impedance analysis and functional status express diagnosis were conducted before and after competitions. Results. The components limiting the operational state of swimmers were determined: "component composition of the body" (44.83% of the total load), "functional" (19.97%).  Correlation relationships were established between the main indicators that determine the level of the operational state of athletes.  The multiple regression equation was calculated, which made it possible to determine the influence of individual significant parameters on the level of the operational state of athletes and the confidence interval.  A group of athletes with operational status indicators below the confidence interval received sport supplementation. Conclusion. The main characteristics of the athletes' operative status are cellular biomarker phase, fat free mass, extracellular water, intracellular water, strength index. These characteristics should be used in assessment of both operative status and complex functional diagnosis of highly-skilled swimmers during competitions.